A new species of amphipod, Megamphopus katagani sp. nov. (Crustacea: Peracarida: Photidae) from the Sea of Marmara (Turkey), with a key to the species of Megamphopus in the North Atlantic, Mediterranean and associated Seas - Bakir, Kerem; Sezgin, Murat; Myers, Alan A. (Zootaxa, 2011)
A new species of amphipod, Megamphopus katagani sp. nov., is described from the sea of Marmara (Turkey). A key to the species of Megamphopus known from the North-East Atlantic, Mediterranean and associated seas is provided.